The Relationship Between Level of Knowledge About Diet With Diabetes Mellitus Diet Compliance at Pangkur Public Health Center, Ngawi Regency - Mulyadi Mulyadi; Didik Mulyono; Sriyatun Sriyatun (Jurnal MIDPRO, 2021)
Diabetes Mellitus (DM) is a non-communicable disease that often causes health problems in the community. One way to avoid complications of DM is to adjust the diet. Adherence to the DM diet is a problem for DM patients in the community. The purpose of this study was to determine the relationship between the level of knowledge about diet with dietary compliance in patients with diabetes mellitus. This research is a quantitative study using a cross sectional design. A sample of 37 respondents was taken using the Simple Random Sampling technique. Bivariate analysis conducted in this study used the Spearman test. The results of the study obtained Pearson correlation with p value = 0.000 <0.05 with a correlation level of 0.779. In conclusion, there is a relationship between the level of knowledge about diet and dietary compliance in patients with diabetes mellitus with a very strong correlation level. Knowledge about diabetes mellitus is one of the factors in increasing dietary compliance in people with diabetes mellitus. Health workers should be more active in involving families in the care of patients with diabetes mellitus.